Mendengarkan Suara Anak (Child’s Voice): Partisipasi Anak dalam Pengambilan Keputusan sebagai Bentuk Kesejahteraan Sosial - Maesun Mia Nur Amalia; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to describe the importance of "Child's Voice" in the context of early childhood well-being, specifically focusing on how child participation in decision-making processes contributes to their social-emotional welfare. While adult perspectives often dominate child-rearing, this research emphasizes that listening to children is a fundamental human right and a core component of subjective well-being. The research method used is a qualitative literature review, analyzing various academic journals and theoretical frameworks related to child agency and participation rights. Implementation results from various literature sources indicate that providing children with opportunities to voice their opinions ranging from daily routines to classroom rules enhances their self-esteem, autonomy, and sense of belonging. The evaluation of this concept shows that active participation acts as a buffer against social exclusion and psychological distress. The results then serve as the basis for formulating follow-up for educators and parents to create a more inclusive and democratic environment. Overall, integrating the child's voice into family and educational settings is a crucial strategy for achieving holistic children's well-being. This is a guideline for writing the Early Childhood Education journal.